The Anti-Mimetic Function of Paratext in Wilkie Collins's Framed Narrative After Dark. - Nayebpour, Karam; Varghaiyan, Naghmeh (Çankaya University Journal of Humanities & Social Sciences, 2023)
The use of mimetic and diegetic modes of storytelling has significant implications for the meaning and interpretation of Wilkie Collins's (1824-1889) short story collection After Dark (1856). By using a framed narrative structure, Collins highlights the mimetic features of the stories in his collection. He creates a semi-factual atmosphere through dividing the story universe into two levels. On the first level, the discourse of the primary narrator and his wife emphasizes the mimetic nature of the six realistic stories recounted on the second level. Through following such a structure, the author seeks to create the illusion that the stories in the collection are biographical accounts. Verisimilitude, or lifelikeness, is therefore presented as the primary narrative property in After Dark. However, as this article mainly argues, the authorial discourse presented in Collins's general preface to the collection--which, to use Gerard Genette's term, is a paratext or threshold--dismantles the characters' realistic pretentions on the two levels of the storyworld. More precisely, by calling the six narrated stories in the collection the offspring of his own imagination, Collins's paratextual preface destroys the highlighted mimetic claims on the two levels in the storyworld.